PENGARUH NEGATIF BUDAYA K-POP TERHADAP SIKAP NASIONALISME PESERTA DIDIK DI SMPN 18 KOTA TANGERANG SELATAN - Eka Susilowati; Sulastri (Yayasan Nusantara Hasana Berdikari, 2023)
The negative cultural influence of K-POP on students' nationalist attitudes is motivated by the existence of Korean cultural imperialism in Indonesia today, where this popular culture is slowly increasingly eroding the typical local Indonesian culture which is the characteristic and identity of the nation, especially among the younger generation of Indonesia, namely teenagers who is a national asset in preserving culture in the future. Today's students are starting to lose their sense of pride in their own nation. They prefer foreign languages ​​to Indonesian, so they often mix Indonesian with other languages. This research is quantitative research and uses a type of correlation research which aims to determine the negative influence of K-POP culture on the attitudes of nationalist students at SMPN 18 South Tangerang City. This research was conducted on students who like K-POP at SMPN 18 South Tangerang City, using a purposive sampling technique. In this research, data collection used questionnaires to determine the negative influence of K-POP culture on students' attitudes. The data analysis technique uses Pearson Product Moment. The correlation test results show a correlation value = (N=104; r= -0.663, Sig.(2-tailed) =0.000, p-value=0.05) which means that between K-POP culture and students' nationalistic attitudes is negative, the correlation strong and significant.